Assessment of Innovative Methods of the Rolling Stock Brake System Efficiency Increasing - Gerlici, Juraj; Gorbunov, Mykola; Kravchenko, Kateryna; Prosvirova, Olga; Lack, Tomáš; Hauser, Vladimír (Manufacturing Technology Journal, 2018)
This paper deals with problem of brake elements unstable operation caused by temperature increase in the friction pair contact during braking. Analysis of constructive solutions for heat dissipation from the brake elements is carried out. It is known that the most used design of ventilated brake disks has disadvantage of creating resistance to movement, which reduces the power of the train. Methods and technical solutions for improving the braking system efficiency by stabilizing the friction contact temperature are investigated. Technical solution dealing with heat removing from the friction surfaces was proposed. Materials with phase transition is used in the design of the braking elements. The expert evaluation system software module in Microsoft Excel was developed to calculate the significance of methods for stabilizing temperature in the friction contact. The expert evaluation results of innovative methods for modern rolling stock brake systems efficiency increase are presented.
Keywords: Brake systems; Temperature of Friction Contact; Stabilization; Expert Evaluations Method